Pengaruh Bauran Pemasaran Terhadap Keputusan Pasien Memilih Rawat Jalan di RSIA Malebu Husada: The Influence of Marketing Mix on Patient Decisions to Choose Outpatient Care at Malebu Husada Hospital - Sukman, Musyarrafah; Haeruddin, Haeruddin; Sumiaty, Sumiaty; Ahri, Reza Aril; Yusuf, Rezky Aulia (Postgraduate Program in Public Health, Universitas Muslim Indonesia, 2022)
Abstract Background: As a health care facility needed by the community, hospitals must be ready and agile to adapt to changes in the number and type of patients who come. This study aims to analyze the effect of the marketing mix on outpatient decisions at Malebu Husada Hospital. Method: This type of research is observational with a cross sectional study design. The population of this study was 1,053 patients and a sample of 100 patients selected by proportionate stratified random sampling. The collected data were analyzed using chi square test and binary logistic regression test. Results: Most respondents were aged 17-35 years (61%), female (79%), college graduates (41%), and private employees (31%). The results of the chi square test analysis show that there is a relationship between marketing mix variables and patient decisions. The results of binary logistic regression analysis show that there are several variables that have no effect on patient decisions. Partially, there is no effect of medical services (p=0.329), supporting services (p=0.055), tariff suitability (p=0.062), payment method (p=0.711), access (easy to reach) (p=0.170), security (p=0.346), comfort (p=0.907), appearance (p=0.307), competence (p=0.923), service procedures (p=0.928), good facilities (p=1. 000), adequate building (p=0.240), attractive building (p=0.193). Variables that have an influence are advertising (p=0.000), responsiveness (p=0.008), suitability of time standards (p=0.005) on outpatient decisions. Simultaneously, the most influential marketing mix variable is responsiveness. Conclusions: The most dominant factor influencing the marketing mix is responsiveness. It is recommended that Malebu Husada Hospital be more disciplined in organizing the work schedule of health workers so that patients do not wait long to get health services. Abstrak Latar Belakang: Sebagai fasilitas pelayanan kesehatan yang dibutuhkan masyarakat, rumah sakit harus siap dan lincah beradaptasi dengan perubahan jumlah dan jenis pasien yang datang. Penelitian ini bertujuan menganalisis pengaruh bauran pemasaran terhadap keputusan pasien rawat jalan di RSIA Malebu Husada. Metode: Jenis penelitian ini adalah observasional dengan rancangan cross sectional study. Populasi penelitian ini sebanyak 1.053 pasien dan sampel sebanyak 100 pasien yang dipilih dengan cara proportionate stratified random sampling. Data yang terkumpul dianalisis dengan menggunakan uji chi square dan uji regresi logistik biner. Hasil: Sebagian besar responden berusia 17-35 tahun (61%), berjenis kelamin perempuan (79%), pendidikan tamat perguruan tinggi (41%), dan pekerjaan pegawai swasta (31%). Hasil analisis uji chi square menunjukkan bahwa ada hubungan variabel bauran pemasaran dengan keputusan pasien. Hasil analisis regresi logistic biner menunjukkan ada beberapa variabel yang tidak ada pengaruhnya terhadap keputusan pasien. Secara parsial menunjukkan tidak ada pengaruh pelayanan medis (p=0,329), pelayanan penunjang (p=0,055), kesesuaian tarif (p=0,062), cara pembayaran (p=0, 711), Akses (mudah dijangkau) (p=0,170), keamanan (p=0,346), kenyamanan (p=0,907), penampilan (p=0,307), kompetensi (p=0,923), prosedur pelayanan (p=0,928), Fasilitas yang baik (p=1.000), bangunan yang memadai (p=0,240), bangunan yang menarik (p=0,193). Variabel yang memiliki pengaruh adalah periklanan (p=0,000), daya tanggap (p=0,008), kesesuaian standar waktu (p=0,005) terhadap keputusan pasien rawat jalan. Variabel bauran pemasaran secara simultan yang paling berpengaruh adalah daya tanggap. Kesimpulan: Faktor paling dominan mempengaruhi bauran pemasaran adalah daya tanggap. Direkomendasikan kepada RSIA Malebu Husada lebih disiplin dalam mengatur jadwal kerja tenaga kesehatan sehingga pasien tidak menunggu lama untuk mendapatkan pelayanan kesehatan.